Separately Continuous Functions on Products and Their Dependence on ℵ Coordinates - Mykhailyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate necessary and sufficient conditions on topological products X = ∏s ∈ s X s and Y = ∏t ∈ T Y t for every separately continuous function f: X × Y → ℝ to be dependent on at most ℵ coordinates with respect to a certain coordinate.